Community-Based Tourism Attraction Development Analysis, Panggul, Trenggalek - Herlina Suksmawati; Praja Firdaus Nuryananda; Leily Suci Rahmatin (Nusantara Science and Technology Proceedings, 2022)
Strategic tourism areas both regionally and nationally have the opportunity to develop conceptualized tourism destinations, such as the existence of Regional Tourism Destinations (DPD/Destinasi Wisata Daerah), hereinafter abbreviated as RTD/DPD Panggul, in Panggul, Trenggalek Regency. This research is important because the development of DPD Panggul involves various tourist attractions that come from resources within the local community, with several supporting facilities for tourism managed by the community, but the level of participation in decision-making and activities in tourism organizations is still not conceptualized in the community. This study has 2 (two) points of urgency, namely empowering the Panggul District community to be more economically empowered and as an entry point for formulating and implementing community-based tourism strategies and local values ??so that there is no brian drain on a larger scale from rural to remote. urban. The mandatory outputs of this research include scientific articles in indexed/accredited national journals and are included as oral presenters at international seminars. This research is in line with one of the six main themes of the research and community service program in 2022. On a regional and regional scale, this research also supports the 2019-2024 East Java RPJMD on Nawa Bhakti Satya, especially on Nawa Bhakti Harmoni, and also supports the Trenggalek Regency RIPPDA 2017-2031 in the tourism sector. As with the research in the first year, concepts such as A4, recreational opportunity spectrum, tourist destinations, tourist attractions, and community-based tourism are still being used. This study uses a qualitative approach with a qualitative descriptive method with the location setting in Panggul District, Kab. Trenggalek. The data collection and data analysis is presented by observation and in-depth interviews.